Dark Energy - Shrestha, Chhabi Kumar (Himalayan Physics, 2015)
This work is focused to investigate the evidence of existence of the dark energy, its composition, its effects, its nature and some theories to explain Dark Energy, estimation of distributed matter and energy in the universe. Dark energy is the most mysterious hypothetical form of energy that indicates the expansion of the universe. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page: 126-130